Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I know that by trial and error it is only possible when $ a=b $, but what is the actual solution process?

share|cite|improve this question
up vote 1 down vote accepted

By Pythagoras


Now subtract $4ab$ on both sides of your equation to see

$$-4ab\cos^2(\theta)=(a+b)^2-4ab=(a-b)^2\ge 0$$

Therefore we must have either $a=b$ or $a,b$ must have different signs. But in the latter case the original equation implies $a=-b$. If $(a,b)\not=(0,0)$, then this also determines the angle $\theta$.

So the only solutions are

$$\left\{\begin{array}{l} a=b, \theta=(2k+1)\frac{\pi}{2}, k\in\mathbb{Z}\\ a=-b, \theta=k\pi, k\in\mathbb{Z}\\ a=b=0, \theta\;\text{arbitrary} \end{array}\right.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.